The Effect of Accounting Information System Use and Accounting Understanding on The Quality of MSME Financial Reports - Nurafni Nurafni; Sultan Sultan; Sofyan Syamsuddin (PT. EQUATOR SINAR AKADEMIA, 2026)
This study aims to analyze the impact of the use of Accounting Information Systems (AIS) and accounting understanding on the quality of financial reports of MSMEs in Palopo City. The method used in this study is a quantitative approach, with primary data obtained through the distribution of questionnaires to MSME actors. The population studied includes all active MSMEs in Palopo City that have been operating for at least three years. The sampling process was carried out using non-probability sampling using the convenience sampling method, resulting in 120 respondents as a sample. Data analysis was performed using multiple linear regression using SPSS version 27. The research findings indicate that individually, the use of Accounting Information Systems does not have a significant impact on the quality of MSME financial reports, while accounting understanding has a positive and significant impact. Collectively, both variables have a significant effect on the quality of financial reports with a coefficient of determination reaching 80.1%. The implementation of this study indicates that improving the quality of MSME financial reports must be done by strengthening accounting understanding and implementing accounting information systems gradually, so that financial management can be more effective, precise, and in accordance with applicable accounting standards.